Circulating Tumor Cells: An Engineered Human Fc‐Mannose‐Binding‐Lectin Captures Circulating Tumor Cells (Adv. Biosys. 7/2017). Issue 7 (July 2017) - Kang, Joo H.; Driscoll, Harry; Mammoto, Akiko; Watters, Alexander L.; Melakeberhan, Bissrat; Diaz, Alexander; Super, Michael; Ingber, Donald E.
Abstract : In article number1700094, Donald E. Ingber and co‐workers present an engineered human Fc‐mannose‐binding lectin (FcMBL), which captures a broad range of circulating tumor cells (CTCs), such as the one shown on the cover, by recognizing cell surface carbohydrates that are expressed on CTCs regardless of whether they have gone through an epithelial‐mesenchymal transition. FcMBL shows high binding affinity to human and animal cancer cells, and successfully captures CTCs from whole blood collected from breast‐tumor‐bearing mice.